Who Would Be Willing to Pay for Energy Transition?: Comparing the Factors for the Public's Willingness to Pay for Transition to Renewable Energy and Nuclear Power - 조석환; 황주성; 김서용 (Journal of Safety and Crisis Management, 2023)
This study aims to analyze what factors influence WTP(Willing To Pay) for cost of development of renewable energy and nuclear power energy. Our research based on the survey data. Our main findings are, first, the public shows a higher willingness to pay(WTP) for renewable energy than that fossil and nuclear energy. Second, WTP for renewable energy is deeply related to not only renewable energy factors such as perceived risk (-), positive image(+) and trust (+), but also fossil energy factors such as perceived benefit (-), positive image (+), trust (-) and knowledge (+). Third, WTP for the development of nuclear energy has been associated with the benefits, risks, images and trust related to nuclear energy. However, variables related to fossil or renewable energy have little impact on WTP for nuclear power energy. While the willingness to pay for renewable energy is influenced by renewable energy as well as fossil fuel factors, the willingness to pay for nuclear energy is s ignificantly influenced by the characteristics of nuclear power itself.
Keywords: energy transition; renewable energy; nuclear energy; willing to pay